Respostas
respondido por:
1
Por adição:
x + y = 9
x - y = 5
2x = 14
x = 14/2 ---> x = 7
x + y = 9 ---> 7 + y = 9 ---> y = 9 - 7 ---> y = 2
S = { 7 ; 2 }
x + y = 9
x - y = 5
2x = 14
x = 14/2 ---> x = 7
x + y = 9 ---> 7 + y = 9 ---> y = 9 - 7 ---> y = 2
S = { 7 ; 2 }
respondido por:
1
x + y = 9
x - y = 5 +
________
2x = 14
x = 7
Substituindo tanto na 1ª ou 2ª
7 - y = 5
- y = 5 -7
- y = -2
y = 2
x - y = 5 +
________
2x = 14
x = 7
Substituindo tanto na 1ª ou 2ª
7 - y = 5
- y = 5 -7
- y = -2
y = 2
sraincrinvel:
S = { 7, 2 }
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás